Toy dance party : being the further adventures of a bossyboots Stingray, a courageous Buffalo, and a hopeful round someone called Plastic - Jenkins, Emily, 1967- (Schwartz & Wade Books, 2008)
Six stories relate further adventures of three best friends, who happen to be toys, as they encounter a fearsome (possible) shark, enjoy a dance party, and deal with rejection by The Girl, who is growing up.